STUDY OF GC/MS PEAK PATTERNS OF 11 COMPOUNDS TYPICAL BURNT SMELL AND THE COMBUSTION PRODUCTS FROM SINGLE MATERIALS - , SHOHIFAH ANNUR, Prof. Dr. Sri Juari Santosa, M. Eng ([Yogyakarta] : Universitas Gadjah Mada, 2011)
There are eleven compounds that give typical burnt smell after accidental fire. These compounds are: 2-hydroxybenzaldehyde, benzylalcohol, acetophenone, 2-methoxyphenol, 2-methyl phenol, 3-methylphenol, 4-methylphenol, 2-hydroxy-5- methylbenzaldehyde, naphthalene, 2-methoxy-4-methylphenol, and 4-ethyl-2- methoxyphenol. The ratio of them in the single material combustion has not been investigated. Combustion experiments with single materials were conducted at 600 Â°C with flow rate 1 L/min of O2. Sixteen kinds of single materials were burnt. They are pine wood, spruce wood, beech wood, meranti wood, oak wood, cotton, cellulose, polyethylene, polypropylene, polystyrene, polyethylene terephthalate, nylon 6-6, epoxy resin, phenolic resin, rubber, and wool. SPME was applied to adsorb the eleven compounds, which were released from the combustion, then the analyses were done in the GC/MS by SIM mode. Screening analyses were carried out by analyzing acetone from gas washing bottle after combustion in the GC/MS by SCAN mode. Single combustion experiments produced different GC/MS peak patterns of 11 compounds. Biomass combustions like woods, cotton, and cellulose resulted in similar peak patterns, high portions of 2-methylphenol, 3-methylphenol, and 4- methylphenol (> 25% of all 11 compounds). Thermoplastic polymers like polyethylene, polypropylene, polystyrene, and nylon 6-6 produced huge portion of naphthalene (>60% of all 11 compounds). In contrast to thermoplastic polymers, thermoset polymers released high portions of 2-methylphenol and 4-methylphenol (> 25% of all 11 compounds) due to the presence of phenolic group in their structure. The rubber sample as elastomer, also produced a high ratio of naphthalene (35.5% of all 11 compounds). Different from rubber, wool sample had 4-methylphenol as the dominant product in the combustion gases (>90% of all 11 compounds). In the screening analyses, the dominant product after combustion is: sugars (>25%) in the biomasses combustion, alkenes (67.5%) in polyethylene combustion, styrene (61.4%) in polystyrene combustion, BTX in polypropylene, rubber, and wool combustion, benzoic acid (35.4%) in polyethylene terephthalate combustion, ketone (48.5%) in nylon 6-6 combustion, and phenols (>58%) in epoxy and phenolic resin combustion .